LEXICAL-SEMANTIC AND STRUCTURAL ANALYSIS OF CONSTRUCTION TERMINOLOGY: ON THE MATERIAL OF THE UZBEK AND ENGLISH LANGUAGES - Raimov Lazizjon Alisherovich (Scholar Express Journal, 2023)
Terminology is one of the specific layers of lectures, which, due to the special structural organization of components, the close internal interconnection of parts, the peculiarity of the formation and development of semantics, the relationship within the terminology and its relationship with other categories of lectures , functioning , and the relationship with the object of nomination , differs from commonly used words and themes . occupies a special place in the structure of the lexical system of the language.
Keywords: Phraseologism; phraseological units; Essay style